Promoting Self-Regulated Learning with Formative Assessment and the Use of Mobile App on Vocabulary Acquisition in Thailand - Budi Waluyo (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Despite extensive studies on self-regulated learning in the past three decades, there is still little research exploring self-regulated learning on foreign language vocabulary acquisition. Therefore, in a classroom-based context, this study explores the effectiveness of a course design that promotes self-regulated learning coupled with formative assessment and the use of Socrative on students’ vocabulary acquisition. The study involves the first-year students (N = 136) taking a general English course at Walailak University, Thailand. On CEFR levels, 68 of them are considered basic users (beginner), while the others are independent users (intermediate). Students’ pre- and post-tests scores as well as students’ total scores from 10 vocabulary tests were examined by using Wilcoxon signed-rank and Mann-Whitney tests. The results disclosed the effectiveness of the course design in enhancing EFL learners’ vocabulary acquisition (Z = -4.055, p = .001, r = .35); however, significant differences were also found across basic and independent users (U = 448.5, p = .001, r = .70). The findings support the ideas that formative assessment reinforces students’ self-regulated learning strategies and students’ levels of English proficiency influence the extent of their self-regulated learning development and involvement.